From deficiency to demand: Consumer preferences for zinc-biofortified rice in Colombia - Oswalt, Sara; Durand-Morat, Alvaro; Rivera, Tatiana; Gallego, Sonia; Andrade, Robert; McFadden, Brandon; Bonatti, Michelle (Elsevier, 2025)
Undernourishment caused by micronutrient deficiencies (hidden hunger) remains a critical global challenge affecting billions worldwide. Approximately 25 % of the population in Colombia has inadequate zinc intake. Biofortification of staple crops, such as rice, offers a promising solution to address this problem. However, changes in the physical and culinary attributes due to biofortification may hinder consumer acceptance and limit the benefits of this approach. This study assesses the impact of zinc fortification, information, and consumer nutrition knowledge on consumers' willingness to pay (WTP) for rice in Cartagena, Colombia. We used a non-hypothetical experimental auction including 400 consumers. The results indicate that, without labelling and information treatment, zinc-biofortified rice is priced equal to premium-quality rice, and at an 18.8 % premium relative to standard-quality rice, highlighting that the high zinc content did not affect rice quality. Labelling results in an increase in WTP for both zinc-biofortified and premium-quality rice but not for standard-quality rice. Information about the benefits of zinc and the problems of zinc deficiency increases the WTP for zinc-biofortified rice by 8.2 % premium relative to premium-quality rice and a 43.8 % premium relative to standard-quality rice, which was reinforced by participants' nutrition knowledge. These findings provide valuable insights for policymakers and stakeholders aiming to address malnutrition effectively, suggesting the implementation of targeted educational initiatives to enhance consumer acceptance, as well as the rice industry and retailers hoping to produce and market biofortified staple crops.